2019
DOI: 10.1097/sle.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Age on Morbidity and Survival Following Laparoscopic Pancreaticoduodenectomy

Abstract: Purposes: To present preliminary perioperative and long-term outcomes in elderly patients compared with younger patients who underwent laparoscopic pancreaticoduodenectomy (LPD).Materials and Methods: A total of 199 patients who underwent LPD were included in this study. The primary data relating to these patients were collected and analyzed in our center from October 2010 to 2017. Results:The intraoperative and postoperative information, including the rate and severity of short-term complications, pathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 25 publications
(32 reference statements)
4
34
0
Order By: Relevance
“…Among the remaining 451 articles, 414 were excluded following title and/or abstract screening according to the inclusion and exclusion criteria. Overall, after full-text review, 8 studies (8,(12)(13)(14)(15)(23)(24)(25) were included in the meta-analysis. The process of selecting relevant studies is presented in Figure 1.…”
Section: Search Results and Article Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the remaining 451 articles, 414 were excluded following title and/or abstract screening according to the inclusion and exclusion criteria. Overall, after full-text review, 8 studies (8,(12)(13)(14)(15)(23)(24)(25) were included in the meta-analysis. The process of selecting relevant studies is presented in Figure 1.…”
Section: Search Results and Article Reviewmentioning
confidence: 99%
“…In total, 4 retrospective studies (14,15,23,24) from China were included in the analysis. 568 patients, who underwent LPD, were included in the analysis.…”
Section: Group 2: Lpd In Elderly and Non-elderly Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in elderly patients who need to undergo pancreaticoduodenectomy, the mortality and morbidity rates were comparable between these two approaches, and LPD might have certain advantages over OPD (116). Similarly, several studies have also shown that LPD is safe and feasible in elderly patients (43,117,118). Topic 14: Follow-up after LPD Statement: Recurrence-free and overall survival after LPD are equal to that after OPD, and both procedures achieve equivalent rates of radical resection margins and number of harvested lymph nodes.…”
Section: Strength Of Recommendation: Strongmentioning
confidence: 99%
“…Most of the studies were underpowered. Long-term outcomes, such as overall survival and disease-free survival, were not systematically reported [27,28].…”
Section: Minimal Invasive Surgery In Pancreatic Cancermentioning
confidence: 99%